In silico and in vitro assessment of TP53, ATM, RAD51, and BAX genes in gastric cancer and their contribution to radiotherapy resistance - Zhang, Junwei; He, Pengtao (Hereditas, 2025)
Background Gastric cancer remains a leading cause of cancer-related morbidity and mortality worldwide. The genetic factors contributing to gastric cancer progression and resistance to therapies, particularly radiotherapy, are not fully understood. TP53, ATM, RAD51, and BAX are genes involved in DNA repair, apoptosis, and response to stress. The aim of this study was to investigate the expression patterns of these genes in gastric cancer, their potential role in radiotherapy resistance, and their diagnostic value. Methodology Gene expression levels of TP53, ATM, RAD51, and BAX were assessed using RT-qPCR across 9 gastric cancer cell lines and 6 normal control cell lines. Additionally, protein expression was confirmed via IHC and TCGA dataset analysis. Methylation levels of these genes were evaluated in gastric cancer tissues using the GSCA database. Mutational analysis was conducted using cBioPortal, and survival analysis was performed using Kaplan-Meier and meta-analysis. The radiotherapy resistance study was carried out by knocking down TP53, RAD51, and BAX in AGS and MKN-45 gastric cancer cell lines, followed by expression analysis, colony formation, and wound healing assays. Results The expression of TP53, RAD51, and BAX was significantly upregulated, while ATM was downregulated in gastric cancer cell lines compared to normal controls. All four genes demonstrated good discriminatory power (AUC = 1) in distinguishing gastric cancer from normal samples. Methylation analysis revealed significant hypomethylation of TP53, RAD51, and BAX, and hypermethylation of ATM in gastric cancer tissues. Mutational analysis showed that TP53 was altered in 88% of gastric cancer samples, while ATM, RAD51, and BAX exhibited lower mutation rates. Survival analysis suggested that elevated expression of TP53, RAD51, and BAX may be linked to poorer survival outcomes, while reduced ATM expression appeared to associate with decreased overall survival. However, these associations require further validation through additional studies. Knockdown of TP53, RAD51, and BAX in AGS and MKN-45 cells resulted in significantly reduced cell proliferation and slower wound healing, highlighting their role in radiotherapy resistance. Conclusion The TP53, RAD51, and BAX genes are significantly involved in gastric cancer progression and resistance to radiotherapy. Their expression and mutation status provide valuable diagnostic and prognostic information.